Balanced Approach Regulatory Measures for Excise Tax on Tobacco and Nicotine-Based Products with Differential Degrees of Harm - Mohamad Hashim, Haswira Nor; Ibrahim, Zuraeda; Ghazali, Noorlaila; Yunus, Nuridayu; Othman, Rani Diana (Universitas Negeri Gorontalo, 2024)
This paper reports a study that analyses regulatory measures for excise tax on tobacco and nicotine-based products in Malaysia.The study highlights current non-optimal nature of excise tax due to a lack of differentiation between the varying degrees of harm caused by different tobacco and nicotine-based products within a given category. The study aims to address this issue by proposing a regulatory measure that adopts a balanced approach to taxing harmful tobacco and nicotine-based products. A focus group discussion involving a group of experts in tax and excise tax, medical and pharmacology, and law and policy was conducted to gather expert inputs on policy compliance with international standards for excise tax on tobacco and nicotine-based products; effectiveness of current policies in addressing harm differentials; and setting excise tax rates to balance harm levels and combat illicit trade. This study concludes that, Malaysia should adopt a balanced approach regulatory measures to combat illicit tobacco trade and promote harm reduction and equitable public health outcomes.This study recommends a differentiated excise tax for tobacco products in Malaysia based on harm and addiction levels, aiming tobalance the excise-duty with differential degrees of harm and optimize policy effectiveness towards achieving a smoke-free Malaysia by 2040. The proposed recommendation is aligned with Article 6 Guidelines of the World Health Organization Framework Convention on Tobacco Control.